دور الميثاق الأخلاقي في تحسين جودة الخدمة التعليمية بمؤسسات التعليم العالي من وجهة نظر أعضاء هيئة التدريس - حسن عبد السلام, علي عمران (Université de M'sila, 2017)
Has the code of ethics, quality of service with great interest by the service organizations and so on different objectives, activities and operations because Machida business environment changes rapidly, and developments, and the current study dealt with one important aspect of it is the role of the Code of Ethics in improving the quality of educational services in higher education institutions, and Temtlt study the problem in answer to the following question: Is there a role for ethical charter to improve the quality of educational service in institutions of higher education? The study aimed to find out the role of the code of ethics to improve the quality of educational service in institutions of higher education, The study population consisted of faculty employed at the Faculty of Economics and Accounting Sabha at the University of members reaching the study sample (31 ) single and then rely on the questionnaire to collect data, and give each paragraph by weight listed in accordance with the scale Likert triple, and then the data using a program analysis (Spss) view to arriving at an appropriate sentence on a sample study in response to the paragraphs of the questionnaire and find out their attitudes, the study results showed a strong relationship between the code of ethics and to improve the quality of educational service was the most important recommendations need to pay attention to improving the quality of educational services and so during the development and modernization of the required standards for the quality of the educational process inputs and outputs, including the existence of a moral charter governs and determines all actions altogether
Keywords: Ethical Charter, Ethics, quality, the quality of educational service.